Early postoperative bleeding after Laparoscopic Roux-En-Y Gastric Bypass: a single center analysis - Rui Pedro Ferreira Santos (2021)
Background: Early postoperative bleeding is a common complication after laparoscopic Roux-En-Y Gastric Bypass (LRYGB) and is associated with significant morbidity. We aimed to identify predictors of early postoperative bleeding after LRYGB and characterize hemorrhagic events and 30-day postoperative outcomes. Methods: We conducted a retrospective cohort study regarding all patients submitted to LRYGB in 2019 at a high-volume obesity center. Early postoperative bleeding was defined as any clinically significant evidence of hemorrhage in the early postoperative period. Demographic, preoperative, and intraoperative factors were evaluated for associations with postoperative bleeding. Postoperative outcomes were compared between patients with and without hemorrhage. Results: Of 340 patients submitted to LRYGB, 14 (4.1%) had early postoperative bleeding. Patients with bleeding had an increased preoperative left hepatic lobe diameter (8.4 vs. 7.3 cm, p=0.048). Prior cholecystectomy (28.6 vs. 14.5%) and previous bariatric surgery (35.7 vs. 23.9%) tended to be more prevalent among these patients. Bleeding occurred at a median time of 31.2 [IQR 19.7-38.5] hours. Thirteen patients presented with intraluminal bleeding and one with extraluminal bleeding. Melena was the most common symptom. All hemorrhages were clinically diagnosed, and 92.9% were managed conservatively. Postoperative bleeding was associated with longer hospital stay (3.5 vs. 2.0 days), higher reintervention (7.1 vs. 0%), and readmission (14.3 vs. 0%), all p<0.05. Conclusions: Bleeding was the most frequent early complication after LRYGB. Patients with hepatomegaly and prior surgeries may have technically challenging LRYGB and should be carefully assessed. Perioperative strategies should be encouraged in high-risk patients to prevent bleeding.